Early Bronze Age pebble installations from Tell es-Safi/Gath, Israel: evidence for their function and utilization. (2nd January 2017) - Eliyahu-Behar, Adi; Shai, Itzick; Gur-Arieh, Shira; Frumin, Suembikya; Albaz, Shira; Weiss, Ehud; Manclossi, Francesca; Rosen, Steve; Greenfield, Tina L.; Greenfield, Haskel J.; Maeir, Aren M.
Abstract : Pebble stone installations are commonly found at various Early Bronze Age sites in the southern Levant. However, their function is often assumed or unknown. Thirteen circular pebble installations were found scattered throughout a residential neighbourhood dating to the Early Bronze Age III at Tell es-Safi/Gath. Five such installations were recently studied by implementing an integrated micro-archaeological approach by which all micro- and macro-artefacts were analysed using various analytical techniques. Based on the analysis of ash-micro remains identified in the sediments, associated plant remains, flint and pottery, we suggest that these installations were used for food-processing, cooking and/or other domestic low-heat tasks. The installations first appear at Tell es-Safi/Gath during the Early Bronze Age III, and seem to disappear during later periods. The functional roles of these installations are discussed in comparison to finds from other Early Bronze Age sites, and of other food preparation traditions known from other periods and cultures.